PENGARUH LITERASI DIGITAL DAN CASHLESS HABIT TERHADAP MINAT BELI PRODUK KULINER UMKM GEN Z DI YOGYAKARTA - Mahri, Fawwaz Lutfi; Tarigan, Nerys Lourensius L (Kajian Ekonomi dan Bisnis, 2025)
This study investigates the influence of digital literacy and cashless habits on the purchasing intentions of Generation Z consumers toward UMKM culinary products in Yogyakarta. The rapid advancement of digital technology has transformed consumption patterns; however, limited digital literacy within this demographic poses challenges related to online transaction security and associated risks. A quantitative methodology, employing multiple linear regression, was used to evaluate the effects of digital literacy and cashless habits on purchasing intention. The sample consisted of 133 respondents, including students, schoolchildren, and other individuals actively engaged in digital technology and cashless transactions. The results demonstrate that both digital literacy and cashless habits significantly affect the purchasing intentions for UMKM products, with the model explaining 60.5% of the variance. These findings provide insights into how improving digital literacy and encouraging cashless habits can enhance the marketing of UMKM products among Generation Z. The study contributes to the understanding of digital consumption behavior and offers recommendations for technology-driven marketing strategies for UMKM.